Inhibition of Cathepsin B by Ferrocenyl Indenes Highlights a new Pharmacological Facet of Ferrocifens. Issue 9 (2nd February 2022) - Sanz Garcia, Juan; Gaschard, Marie; Navizet, Isabelle; Sahihi, Mehdi; Top, Siden; Wang, Yong; Pigeon, Pascal; Vessières, Anne; Salmain, Michèle; Jaouen, Gérard
Abstract: The family of ferrocifens initially built up from the anti‐oestrogen tamoxifen shows a broad antitumor activity both in vitro and in vivo . Their mechanism of action relies on the presence of the redox motif [ferrocene‐ene‐phenol] that, under oxidative conditions, generates reactive oxygen species (ROS) and affords electrophilic quinone methides (QMs) having the ability to alkylate biological nucleophiles and in turn elicit a strong antiproliferative activity. In this context, the cysteine protease cathepsin B was initially presumed to be a target for ferrocenyl QMs. In vitro enzymatic assays ruled out this hypothesis but unexpectedly revealed that other ferrocifen metabolites, i. e. ferrocenyl indenes, acted as moderate inhibitors of cathepsin B. These experimental results were nicely confirmed by molecular docking calculations, that showed that the monophenol ferrocenyl indene and to a lower extent the diphenol interacted with the active site of cathepsin B, making it an unanticipated target of ferrocifens. Abstract : Ferrocenyl indenes resulting from oxidation of ferrocifen mono‐ and diphenols act as moderate inhibitors of the lysosomal enzyme cathepsin B as highlighted by in vitro enzymatic assays. These experimental results are substantiated by molecular docking calculations that position the active complexes in the active site of the enzyme.